Quarter-wavelength side-coupled ring filter with open stubs for narrow dual-band / Nur Azreezan Muhamad Snin - Muhamad Snin, Nur Azreezan
In this paper, a combination of a side-coupled ring resonator with two open stubs is proposed to exhibit a dual band filter response. The dual band filter is fabricated on FR4 microstrip substrate and the measurement results are found to be coherent to the simulation.